Using Tasks to Assess Spanish Language Learning (GIST – Education and Learning Research Journal, 2011)
The methodology of Task-based teaching (TBT) has been positively regarded by many researchers and language teachers around the world. Yet, this language teaching methodology has been mainly implemented in English as a second language (ESL) classrooms and in English for specific purpose (ESP) courses; and more specifically with advanced-level learners. The present experimental research study aimed at proving the feasibility of a Task-Based Assessment (TBA) approach in a different learning context: A beginning Spanish class. That is to say, contrary to the traditional TBT-TBA implementation, the experiment was conducted in a foreign language class with students bearing a low level of language proficiency. The research produced positive results in terms of students’ linguistic and communicative performance.
Keywords: Task; Task-Based Teaching (TBT); Task-Based Assessment (TBA).